GENOPROTECTIVE EFFECTS OF ETHANOLIC STEM EXTRACTS OF TINOSPORA CORDIFOLIA ON SODIUM ARSENITE-INDUCED DNA DAMAGE IN SWISS MICE LYMPHOCYTES BY COMET ASSAY - AMBASTA SK; SHASHIKANT; SINHA UK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The study was aimed to evaluate the DNA protective effects of ethanolic extracts of Tinospora cordifolia stem on Swiss albino mice lymphocytes against the sodium arsenite-induced genotoxicity. Methods: In this experiment, 25 animals of nearly the same age were equally divided. Group 1 (control) fed on tap water while rest four (2, 3, 4, and 5) groups were treated with 4 mg/kg body weight, per orally sodium arsenite for 12 weeks. Sodium arsenite pretreated groups (4 and 5) were followed by administration of 80 mg/kg body weight, per orally T. cordifolia extracts for the next 12 weeks. Animals were sacrificed at the 8th week and 12th week, respectively, for the assessment of sodium arsenite-induced genotoxicity and comparative genoprotective effects of experimental plant extracts. The extent of DNA migration is directly proportional to the magnitude of DNA damage. Percentage tail DNA content and olive tail moment parameters were used in the comet to relate DNA damage. Results: The findings suggested that the ethanolic stem extracts of T. cordifolia significantly inhibited the sodium arsenite-induced oxidative genotoxicity. The phytoconstituents of T. cordifolia shown to retard genetic damage associated with arsenic exposure. Conclusion: T. cordifolia may be used as a preventive herbal preparation against chemical or arsenical toxicity.